2017
DOI: 10.1016/j.jnucmat.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of grain size in He bubble formation: Implications for swelling resistance

Abstract: Nanocrystalline metals are postulated as radiation resistant materials due to their high defect and particle (e.g. Helium) sink density. Here, the performance of nanocrystalline iron films is investigated in-situ in a transmission electron microscope (TEM) using He irradiation at 700 K. Automated crystal orientation mapping is used in concert with in-situ TEM to explore the role of grain orientation and grain boundary character on bubble density trends. Bubble density as a function of three key grain size regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 78 publications
1
28
0
1
Order By: Relevance
“…Nanocrystalline metals are considered candidates for severe environmental applications which require irradiation-resistant materials 1 , 2 due to a promise of enhanced mechanical properties (strength and ductility) 3 , 4 , and radiation resistance 1 , 2 , 5 11 due to their high grain boundary density in comparison to their bulk counterparts 3 , 4 , 12 . During applications involving radiation, such as fusion and fission reactors, materials are exposed to different energetic particles with a range of doses and dose rates, which form Frenkel defect pairs (vacancies and interstitials); a high percentage of these defects will recombine leaving a small ratio of freely migrating defects.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocrystalline metals are considered candidates for severe environmental applications which require irradiation-resistant materials 1 , 2 due to a promise of enhanced mechanical properties (strength and ductility) 3 , 4 , and radiation resistance 1 , 2 , 5 11 due to their high grain boundary density in comparison to their bulk counterparts 3 , 4 , 12 . During applications involving radiation, such as fusion and fission reactors, materials are exposed to different energetic particles with a range of doses and dose rates, which form Frenkel defect pairs (vacancies and interstitials); a high percentage of these defects will recombine leaving a small ratio of freely migrating defects.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it has been reported that He irradiation of Fe nanocrystals resulted in bubble accumulation dependent on crystal size with smaller crystals accumulating He bubbles at lower concentrations and with reduced irradiation hardening compared to the bulk [43]. El-Atwani et al [21,44] observed reduced bubble density in nanocrystalline W grains (<100 nm grain sizes) compared to ultrafine W (100–500 nm grain size range) which they attributed to the proximity of the grain boundary in nanocrystalline W acting as a sink for defects. These studies indicate that the effectiveness of interphases will depend on the distances defects migrate within the boundary planes and thus a shorter required distance in smaller crystals enhances the recombination of point defects at sinks.…”
Section: Resultsmentioning
confidence: 99%
“…Averages were calculated from the results in all grains. A detailed illustration of the quantification process was published in the supplemental of reference [20]. Figure 1 shows a schematic diagram of the sample, implantation conditions and overlapping ion and displacement damage distributions.…”
Section: Methodsmentioning
confidence: 99%